Rekam Jejak Kepemimpinan Kharismatik I Aba Jadjid Bostan Daeng Mamadja sebagai Karaeng Galesong XVII (1952-2009) - Hidayat, Irwan; Bahri, Bahri; Najamuddin, Najamuddin (Universitas Syiah Kuala, 2025)
Throughout its history, the Kingdom of Galesong has been led by 19 rulers, known as Karaengs or Traditional Leaders. This study focuses on the leadership of I Aba Jadjid Bostan Daeng Mamadja, the 17th Karaeng of Galesong, who held the longest reign from 1952 to 2009. Prior to becoming king, he had already proven and shaped his leadership through a series of heroic events that built his reputation and image as a charismatic leader. This research employs a qualitative method with a historical approach. The findings indicate that the formation of I Aba Jadjid Bostans charismatic leadership was influenced by both external (destiny or birthright) and internal (deliberate formation through rigorous training) factors, in line with Max Webers theory. His leadership experienced significant shifts in the role and function of a Karaeng. From 1952 to 1962, as Karaeng of Galesong, he acted both as the head of government in an administrative sense and as the leader of the kingdoms traditional community. However, from 1962 to 2009, his authority was reduced to leading only the kingdoms customary community due to changes in Indonesias governmental structure. Throughout his reign, he was known as a deeply respected and beloved Karaeng, admired for his wisdom, strong character, and charismatic presence. It is therefore unsurprising that his leadership left a lasting legacy, particularly in preserving the existence of the Kakaraengang institution and the cultural traditions of Galesong.